The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1071/ch10214
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Based 'Click' Chemistries in Polymer: Synthesis and Modification

Abstract: A series of thiol-based ‘click’ reactions is discussed with an emphasis on highlighting the individual chemistries and noting recent literature examples. This is not an exhaustive review but rather serves to demonstrate the versatility and clear potential of thiol-based chemistry in polymer/materials design, synthesis, and modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 92 publications
0
47
0
Order By: Relevance
“…Amato et al 23 have very recently shown that thiol-yne miniemulsion polymerizations are also possible. [13][14][15][16][17]24,[27][28][29][30][31][32] In our previous communications outlining the use of thiol-ene suspension polymerizations we focused on a limited set of monomers, used photoinitiation, and examined a range of surfactants and stabilizing agents. [13][14][15][16][17][24][25][26] High reaction rates, multiple modes of initiation (photo-, thermal, and redox), the ease of synthesis in a waterbased medium, and the facile compositional tunability afforded by many thiol, ene, and yne monomers and polymers offers numerous opportunities for such materials to be utilized in a variety of elds and applications.…”
Section: Introductionmentioning
confidence: 99%
“…Amato et al 23 have very recently shown that thiol-yne miniemulsion polymerizations are also possible. [13][14][15][16][17]24,[27][28][29][30][31][32] In our previous communications outlining the use of thiol-ene suspension polymerizations we focused on a limited set of monomers, used photoinitiation, and examined a range of surfactants and stabilizing agents. [13][14][15][16][17][24][25][26] High reaction rates, multiple modes of initiation (photo-, thermal, and redox), the ease of synthesis in a waterbased medium, and the facile compositional tunability afforded by many thiol, ene, and yne monomers and polymers offers numerous opportunities for such materials to be utilized in a variety of elds and applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reviews have covered much of the thiol-based chemistry that could be discussed here. [77][78][79][80][81][82]105,106] As such only more recent, select examples will be given to demonstrate the power of these thiol-based reactions.…”
Section: Raft and Thiol-based Reactionsmentioning
confidence: 99%
“…[77][78][79][80][81][82] Many of these reactions are accurately classified as click reactions and include examples from the thiol-ene (including the thiol-Michael variant), [77,[83][84][85][86][87][88][89][90][91][92][93] thiolyne, [78,85,[92][93][94][95][96][97][98] thiol-isocyanate, [99,100] thiol-halo, [101][102][103] and thiol-oxirane reactions, [104] Figure 4. Of these the radical-mediated thiol-ene reaction is currently the most widely employed in polymer synthesis and modification.…”
Section: Raft and Thiol-based Reactionsmentioning
confidence: 99%
“…[106] Reactions of Polymeric Thiols Thiol-Ene Reactions In recent years, many thiol-based reactions have been recognized and used as highly efficient processes for polymer synthesis and functionalization. [109][110][111][112][113][114][115] The increasing number of routes available to transform the thiocarbonylthio end-group to a thiol provides an avenue to explore and exploit chemistry on the thiol functional 'handle'. Examples of reactions that can be performed at the terminal thiol group in RAFT-prepared (co)polymers include thiol-ene, [72][73][74]109,[116][117][118][119][120][121][122] thiolyne, [72,110,118,[123][124][125][126][127][128] thiol-isocyanate, [129,130] thiol-halo [77] and thiol-oxirane [67] reactions, many of which possess the key characteristics of click reactions.…”
Section: Thermal Eliminationsmentioning
confidence: 99%